PROGRAM BERSIH SEHAT BERSAMA KKN STAIN MADINA KELOMPOK 30 TAHUN 2023 - Septrisia, Reni; Habibi, Anwar; Nst, Purnama Sari; Abdullah, Iqbal Alan; Lubis, Ibnu Akhyar; Mardiah, Sangkot Rabiah; Juniawati, Eva; Sukriani, Liza; Suriati, Irna; Nst, Rizky Solatiah Yasin (Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2023)
Objective. The activity, namely the Real Work Lecture (KKN) by Group 30 of STAIN MADINA, has been carried out in Siunggam Julu Village in a Southeast Padang Bolak District and is in North Padang Lawas Regency and is in North Sumatra Province. The main challenge faced by Siunggam Julu villagers is the lack of awareness of the importance of protecting the environment. They often do not pay attention to proper waste disposal sites and tend to litter, especially into the river and its surroundings. Materials and Methods. The materials we use at this stage are tools that will be used in disposing of organized waste bins with the method of collecting data through observations, surveys through interviews and literature research to find the right strategic points in an effort to create separate waste bins based on the type of waste (wet and dry waste), as well as providing education and socialization to the community about the importance of waste sorting. Results. After successfully establishing an organized waste disposal site in Siunggam Julu Village, we realized that helping villagers understand the concept of sorting waste by type is very important in maintaining a clean and healthy environment. Conclusion. Through this hygiene activity in Siunggam Julu village we realized the need for a complex understanding of how important differentiated waste disposal bins are.